Pencemaran merkuri di perairan dan karakteristiknya: suatu kajian kepustakaan ringkas - M. Adlim (Depik, 2016)
Abstract. The issue of mercury pollution in Aceh waters, Indonesiadue to gold mining activities hasbeen a polemic in local media and Aceh Local Government and the communities have much concern on this case. The impact of mercury pollution in the Teunom and Tangse (Aceh)rivers was often assumed that it has similarity with Minamatapollution in Japan. This article intends to enlighten the characteristic mercury either as elements or compounds including methyl mercury which is highly toxic. Gold mining using elemental mercury is poorly soluble in water, the solubility is only 0.06 g per ton of mercury but the solubility can increase indark the sea-bed and ina lot of dissolved oxygen. Based on the properties of solubility, it is understood that the mercury levels in the Teunom and Tangse rivers still below the tolerance limit, but the gold mining activities still bringsthe risk of environmental damage especially inadequate supervision. Many researchers were trying to prove the natural conversionfrom mercury into methyl mercury (biomethylation) but they usedthe salt instead of the elemental mercury in their experiments. Methyl mercury is found in nature, but the process mercury conversion into methyl mercury compound is still controversial and it has not obtained adequate evidence for the natural alteration,therefore gold pollution which is due to releasing elemental mercury into environment might not be analogue to Minamata case.Keywords: Aceh; Methyl-mercury; Minamata; Mining; GoldAbstrak. Informasi pencemaran merkuri di perairan Aceh dan kaitannya dengan aktivitas pertambangan emas telah menjadi polemik sehingga menjadi perhatian Pemda Aceh dan Masyarakat. Dampak pencemaran merkuri di Sungai Teunom dan Tangse sering dianalogikan dengan kasus pencemaran merkuri di teluk Minamata, Jepang. Artikel ini bermaksud memberi pencerahan kharakteristik merkuri baik sebagai unsur maupun sebagai senyawa seperti metil merkuri yang sangat beracun. Penambangan emas menggunakan unsur merkuri yang sukar larut dalam air, kelarutannya hanya 0,06 g per ton unsur merkuri namun kelarutannya dapat meningkat jika di dasar laut yang gelap dan banyak oksigen terlarut. Berdasarkan sifat kelarutannya, dapat dipahami bahwa kadar merkuri di Sungai Teunom masih di bawah batas toleransi, namun aktivitas penambangan emas tetap saja memiliki resiko kerusakan lingkungan apalagi jika tidak mendapat pengawasan yang memadai. Banyak peneliti berusaha membuktikan perubahan merkuri menjadi metil merkuri (biometilasi) tetapi mereka menggunakan garam merkuri dan bukan unsur merkuri dalam ekperimen mereka. Metil merkuri memang ditemukan di alam tetapi proses perubahan dari senyawa merkuri menjadi metil merkuri masih diperdebatkan dan belum diperoleh bukti yang kuat perubahan dari unsur merkuri menjadi metil merkuri dalam air sehingga di Peraian Aceh belum tentu tercemar metil merkuri sebagaimana kasus Minamata.Kata kunci: Aceh; metil-merkuri; minamata; penambangan; emas